Endogenous temporal attention in the absence of stimulus-driven cues emerges in the second year of life. - Anna Martinez-Alvarez; Ferran Pons; Ruth de Diego-Balaguer (PLoS ONE, 2017)
Anticipating both where and when an object will appear is a critical ability for adaptation. Research in the temporal domain in adults indicate that dissociable mechanisms relate to endogenous attention driven by the properties of the stimulus themselves (e.g. rhythmic, sequential, or trajectory cues) and driven by symbolic cues. In infancy, we know that the capacity to endogenously orient attention progressively develops through infancy. However, the above-mentioned distinction has not yet been explored since previous studies involved stimulus-driven cues. The current study tested 12- and 15-month-olds in an adaptation of the anticipatory eye movement procedure to determine whether infants were able to anticipate a specific location and temporal interval predicted only by symbolic pre-cues. In the absence of stimulus-driven cues, results show that only 15-month-olds could show anticipatory behavior based on the temporal information provided by the symbolic cues. Distinguishing stimulus-driven expectations from those driven by symbolic cues allowed dissecting more clearly the developmental progression of temporal endogenous attention.